Cuidado integral a recién nacido con hiperbilirrubinemia neonatal: análisis de caso clínico - Patiño Capa, Anggie Jamilex; Arredondo Zapata, Tahis Fernanda (My University, 2024)
Neonatal hyperbilirubinemia is a common condition that, without timelytreatment, can cause serious complications such as kernicterus. The aimof thisstudy was to design a nursing care plan based on the NANDA-NIC-NOCtaxonomyfor a neonate with unconjugated hyperbilirubinemia at the Hospital General TeófiloDávila (Ecuador). A descriptive and observational approach was used, analyzingthepatient's clinical history and current literature. Interventions includedLEDphototherapy, neurological monitoring, eye protection, thermal control, breastfeedingpromotion and caregiver education. After 48 hours, total bilirubin decreasedby33.8% without complications. The Nursing Care Process allowed standardizingcare, identifying risks and improving family satisfaction. It is concluded that theroleofnursing is key in the prevention of kernicterus through timely, systematicandhumanized interventions, adapted to the Ecuadorian hospital context.
La hiperbilirrubinemia neonatal es una condición frecuenteque, sin tratamiento oportuno, puede causar complicaciones gravescomoelkernicterus. Este estudio tuvo como objetivo diseñar un plan decuidadosdeenfermería basado en la taxonomía NANDA-NIC-NOC para unneonatoconhiperbilirrubinemia no conjugada en el Hospital General TeófiloDávila(Ecuador). Se empleó un enfoque descriptivo y observacional, analizandolahistoria clínica del paciente y literatura actual. Las intervencionesincluyeronfototerapia LED, monitorización neurológica, protección ocular, controltérmico, fomento de la lactancia materna y educación a cuidadores. Tras48horas, la bilirrubina total descendió un 33.8 % sin complicaciones. ElProceso de Atención de Enfermería permitió estandarizar cuidados, identificar riesgos y mejorar la satisfacción familiar. Se concluye que el rolde enfermería es clave en la prevención del kernicterus mediante intervenciones oportunas, sistemáticas y humanizadas, adaptada sal contexto hospitalario ecuatoriano.
Keywords: HIPERBILIRRUBINEMIA NEONATAL; FOTOTERAPIA; CUIDADOS DE ENFERMERIA; KERNICTERUS